Necessity of Electroencephalography in High-risk Brief Resolved Unexplained Event - Hepsen Mine Serin; Erdem Şimsek; Özge Altun Köroğlu; Seda Kanmaz; İpek Dökürel Çetin; Demet Terek; Sanem Yılmaz; Gül Aktan; Hasan Tekgül; Nilgün Kültürsay; Sarenur Gökben (Galenos Yayinevi, 2019)
Aim:A brief resolved unexplained event (BRUE) is characterized by sudden alterations in an infant's breathing, color, tone, or responsiveness. The aim of this study was to evaluate the necessity of electroencephalography (EEG) in high-risk BRUE cases.Materials and Methods:Fifty-one patients' cases were analyzed retrospectively. All of these patients were younger than 1 month so considered to be a high-risk group. The gestational week, the age of the patient, the duration of the event, the conditions related to the event, whether or not any intervention was needed, the type of intervention if done, if the event recurred, the number of recurrences, the state of consciousness during the event, respiratory pattern, muscle tone, sleeping position, suspicion of trauma, use of medication by mother and/or baby and smoking exposure were evaluated in detail.Results:The mean age of the patients was 15.74±14.96 days, 31 (60.78%) were male and 20 (39.21%) were female. The mean gestational age was 37.64±2.35 weeks. The neurological examinations of the patients were evaluated as normal. EEG was performed in 36 (70.58%) of the 51 patients and only one patient had sharp waves in the left hemisphere central region. In 11 patients hospitalized with a preliminary diagnosis of BRUE, final diagnoses were found as congenital pyloric stenosis, dehydration, fetal myocarditis, patent ductus arteriosus, lower respiratory tract infection and gastroesophageal reflux.Conclusion:It would be more appropriate to plan the tests to be carried out in the high-risk BRUE group by evaluating many factors such as recurrence of the event, family history, and neurological examination findings. As a result, even in the high-risk BRUE group, it would be cost effective to perform an EEG if only the clinical cues are strongly suggestive for the diagnosis of epilepsy.